Analysis of the Protection of Workers' Rights in Mass Termination of Employment (Mass Layoffs) in the Omnibus Law Era (A Case Study of the Indonesian Manufacturing Industry Sector) - Kendelif Kheista (Media Hukum Indonesia (MHI), 2026)
The enactment of Law No. 6 of 2023 on Job Creation has triggered a fundamental shift in the internal procedures governing mass redundancies in Indonesia. This study will examine the effectiveness of worker protection in the manufacturing sector following the implementation of this regulation, using a normative legal approach. Field findings indicate that certain procedures have been streamlined for the sake of business efficiency; conversely, this simplification has created legal loopholes that undermine the right to severance pay and job security. The author emphasises the need for a re-evaluation of labour oversight to uphold the integrity of worker protection amidst the current wave of investment.